Determination of the stages of the injection process for Common Rail injectors using vibration pulses. Issue 1 (December 2020) - Belchev, Sergey; Ivanov, Zdravko; Uzuntonev, Trifon; Mihaylov, Veselin
Abstract: The study and modeling of the combustion process of diesel engines require knowledge of the injection characteristics. The information on the exact start, duration and end of the injection is required. For Common Rail injectors with electromagnetic control, the beginning and duration of the electronic control pulse are precisely known. The actual start and duration of the injection are not the same as those of the impulse and they are related to the movement of the nozzle needle. The experimental determination of the movement of the nozzle needle requires specially prepared experimental installations and expensive measuring instruments. In addition, the experimental injector must be prepared with design modifications allowing the incorporation of sensors. The article presents a method for determining the start and duration of injection of Common Rail injectors using the registration and analysis of vibration pulses generated in the injector body. The method is based on the fact that the nozzle needle causes vibrations in the injector body when lifting and seating.